Listening and note-taking skills - Dunkel, Patricia A.; Lim, Phyllis L.; Pialorsi, Frank; Bonesteel, Lynn.; Espeseth, Miriam; Mackey, Daphne (London: Heinle Cengage, 2014)
"The new edition of the Listening and Notetaking Skills series incorporates engaging National Geographic content and video featuring authentic interviews and videos with National Geographic Explorers! This unique approach engages learners while enhancing listening comprehension and developing notetaking and study skills"--Publisher.
DVD: The gift of traveling --Palenque --An actor and a travel writer --Digital nomad --The human journey.
Videodisc is in English, with optional English subtitles.
Videodisc contains interviews with Annie Griffiths Belt, George Stuart, David Stuart, Andrew McCarthy, Spencer Wells.
Keywords: English language -- Textbooks for foreign speakers; Discoveries in geography -- Problems, exercises, etc; Note-taking -- Problems, exercises, etc; Listening comprehension tests; Readers -- Geography; Explorers -- United States -- Interviews; English language -- Study and teaching -- Audio-visual aids